On Commutative Characterization of Graph Operation with Respect to Metric Dimension - Liliek Susilowati; Mohammad Imam Utoyo; Slamin Slamin (Journal of Mathematical and Fundamental Sciences, 2017)
Let  G be a connected graph with vertex set V(G) and W={w1, w2, ..., wm} âŠ† V(G). A representation of a vertex v âˆˆ V(G) with respect to W is an ordered m-tuple r(v|W)=(d(v,w1),d(v,w2),...,d(v,wm)) where d(v,w) is the distance between vertices v and w. The set W is called a resolving set for G if every vertex of G has a distinct representation with respect to W. A resolving set containing a minimum number of vertices is called a basis for G. The metric dimension of G, denoted by dim (G), is the number of vertices in a basis of G. In general, the comb product and the corona product are non-commutative operations in a graph. However, these operations can be commutative with respect to the metric dimension for some graphs with certain conditions. In this paper, we determine the metric dimension of the generalized comb and corona products of graphs and the necessary and sufficient  conditions of the graphs in order for the comb and corona products to be commutative operations with respect to the metric dimension.